Sistem Informasi Pelayanan Posyandu (Si Papos) Pada Desa Tegalsari Karawang - Eka Chandra Ramdhani; Jodi Gustian Ilham; Asep Asep; Juniarti Eka Sapitri (JISICOM (Journal of Information System, Informatics and Computing), 2021)
Health is the main thing for mankind because with optimal health, everyone will live productively in social or economic aspects. With the increase in various types of diseases experienced by the community, resulting in a decrease in the percentage of health in the community so that a comprehensive solution needs to be carried out and touches every community even from an early age (toddlers). Until now, the management and processing of data at the posyandu in Tegalsari Village, Kab. Karawang still uses a paper-based mechanism so that problems are still found, especially in terms of accuracy, transparency and effectiveness. The software development method used in making the information system is a prototype then using PHP and My sql and the tool used in designing this information system is UML.